2022
DOI: 10.3390/jcm11164896
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Related ARDS: Key Mechanistic Features and Treatments

Abstract: Acute respiratory distress syndrome (ARDS) is a heterogeneous syndrome historically characterized by the presence of severe hypoxemia, high-permeability pulmonary edema manifesting as diffuse alveolar infiltrate on chest radiograph, and reduced compliance of the integrated respiratory system as a result of widespread compressive atelectasis and fluid-filled alveoli. Coronavirus disease 19 (COVID-19)-associated ARDS (C-ARDS) is a novel etiology caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 170 publications
0
15
0
Order By: Relevance
“…Analysing which clinical predictors might reveal patients at higher risk of PNX development we found that the most important clinical index was the P/F ratio, identifying that a more severe respiratory failure condition at admission was likely to predict PNX occurrence. In particular, patients with a low P/F ratio (<200) were more prone to develop PNX and had a poorer prognosis compared to survivors (median value 106 [56–309] vs 266 [192–304]; p = 0.004) [ 35 , 36 ]. Another important observation from our data suggests that ventilatory support was a predictor of PNX development.…”
Section: Discussionmentioning
confidence: 99%
“…Analysing which clinical predictors might reveal patients at higher risk of PNX development we found that the most important clinical index was the P/F ratio, identifying that a more severe respiratory failure condition at admission was likely to predict PNX occurrence. In particular, patients with a low P/F ratio (<200) were more prone to develop PNX and had a poorer prognosis compared to survivors (median value 106 [56–309] vs 266 [192–304]; p = 0.004) [ 35 , 36 ]. Another important observation from our data suggests that ventilatory support was a predictor of PNX development.…”
Section: Discussionmentioning
confidence: 99%
“…Lung ultrasound examination was performed using standard ultrasound machines: 1 ) LOGIQ e, GE Healthcare, Milwaukee, 2 ) Lumify, Philips Ultrasound, Inc. Bothell, or 3 ) MyLabGamma, Esaote, Genoa, Italy. A linear array transducer (5.0–12.0 MHz) was used to examine six regions per hemithorax, according to previously described protocols ( 16 , 18 ). To determine the regions, the chest is divided into anterior, anterolateral, and posterior of the axillary line.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, based on previous findings that biomarker levels differ among ARDS subgroups, we postulated that endothelial dysfunction would have a stronger association with edema in patients with nonpulmonary causes of ARDS, whereas alveolar epithelial injury would be more strongly associated with pulmonary edema in patients with pulmonary ARDS, including COVID-19 related ARDS. The latter presents with a distinct clinical image of severe alveolar edema combined with pulmonary microthrombosis ( 16 ), indicating both epithelial and endothelial injury. The rationale for investigating COVID ARDS separately was thus to examine potential differences in the studied associations compared with other forms of pulmonary ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…With over 610 million reported human infections and 6.5 million deaths 1 , SARS-CoV-2, also denoted 2019-nCoV, is a positive-sense single-stranded RNA enveloped virus responsible for the ongoing COVID-19 pandemic. The virus mainly infects the respiratory system, where it can cause acute respiratory distress syndrome (ARDS) and fatal respiratory failure in some patients 2 , and it can also have long-lasting effects on other organs and systems, including long-term comorbidities (neurological disorders, memory loss, gastrointestinal distress, fatigue, insomnia, dyspnea) and post-acute sequelae of COVID-19 (PASC) 3–5 . Given the spread and severity of the disease, it is crucial to develop efficient treatments and rapidly available solutions that can supplement active immunisation efforts, which are still challenged by high viral transmissibility, re-infection, and immune escape variants 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%